Contribution of Cloud Accounting to Employment and Economic Growth: An Evaluation from Nigerian Public Sector - Ayoola Azeez Olaoye (Business & Management Compass, 2024)
Statistically, the global unemployment rate has drastically reduced due to emergency of cloud accounting. This research therefore evaluates the contribution of cloud accounting to economic growth and employment creation from the Nigerian public sector perspective. Analyzing secondary data from 2016 to 2022, the study identifies several significant findings. The data obtained were analyzed using descriptive statistics and time series data containing ordinary least square technique. The results highlight a positive and statistically significant correlation between the adoption rate of cloud accounting, the number of cloud accounting software providers, and the General Cloud Accounting Metric. These findings underscore the pivotal role of cloud accounting in fostering economic growth in Nigeria through job creation and facilitating informed decision-making with remote financial information. However, it's crucial to acknowledge that Nigeria's annual adoption rate of cloud accounting remains relatively low. Therefore, the study recommends concerted efforts to accelerate and improve the adoption of cloud accounting in Nigeria.